Inelastic buckling assessment of monosymmetric I-beams having stepped and non-compact flange sections. (November 2015) - Surla, Albert S.; Kang, Sung Yong; Park, Jong Sup
Abstract: This paper presents the finite element analyses made which determine the inelastic buckling capacity of monosymmetric stepped I-beams under uniform bending. The stepped beams analyzed have non-compact flanges and varying degree of symmetry about the x-axis. Beams with degree of symmetry, ρ, of 0.1 to 0.9 with an interval of 0.2 are investigated for this study. Both doubly stepped and singly stepped beam configurations are analyzed. To determine the inelastic buckling strength of the beams, nonlinear analysis is performed using the finite element program ABAQUS. Different design standards such as AISC, AS4100 and EN1993 are then used to compare the strengths of prismatic and stepped beams. The results from the comparisons are also used to check the accuracy of the values obtained from finite element analysis. The results showed that finite element analysis can be a very useful tool in determining the inelastic buckling capacity of stepped beams. Also, the comparisons for the stepped beams analyzed with stepped length parameter α of 0.25, 0.333 and 0.5, with increase in flange thickness of about 20–80% and no increase in flange width, showed that there is about a 10% increase in the buckling strength when the beams are stepped. The new stepped beam correction factor, C nfist m, is then introduced to take into account the increase in strength when the beams are stepped. Highlights: Inelastic lateral–torsional buckling of stepped beams having non-compact flanges. Equal end moments are used as the loading condition for all the beams analyzed. Finite element modeling is used to determine the buckling strength of the beams. Buckling strength trends of prismatic and stepped beams are compared. A new correction factor for inelastic buckling of stepped beam is proposed.